2020
DOI: 10.1039/c9cp05019a
|View full text |Cite|
|
Sign up to set email alerts
|

p-Type conductivity mechanism and defect structure of nitrogen-doped LiNbO3 from first-principles calculations

Abstract: The charge-state transition level and geometry structure of non-metallic N-doped LiNbO3 are calculated by DFT, which reveal the p-type conductivity mechanism of LiNbO3:N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Samples and raw materials needed in the NCM ternary cathode material experiments are of high cost, and some experiments may be conducted several times; thus, the entire experiment will need a long time. However, based on firstprinciples [16][17][18], the physical and electrochemical properties can be calculated and analyzed by Materials Studio, Nanodcal, and MATLAB; the results can give some theoretical advice or investigation directions about the relevant experiments, and the theoretical calculation can effectively shorten the whole investigation period and reduce the cost [16]. In this article, the Na-doped layer-structure Li 1−x Na x Ni 1/3 Co 1/3 Mn 1/3 O 2 is studied theoretically with density functional theory of firstprinciples; the results show that the electrochemical performance of Li 1−x Na x Ni 1/3 Co 1/3 Mn 1/3 O 2 is affected by the proportion of Na-substitution and the best proportion of Nasubstitution in LiNi 1/3 Co 1/3 Mn 1/3 O 2 is in agreement with that of experiments [15].…”
Section: Introductionmentioning
confidence: 99%
“…Samples and raw materials needed in the NCM ternary cathode material experiments are of high cost, and some experiments may be conducted several times; thus, the entire experiment will need a long time. However, based on firstprinciples [16][17][18], the physical and electrochemical properties can be calculated and analyzed by Materials Studio, Nanodcal, and MATLAB; the results can give some theoretical advice or investigation directions about the relevant experiments, and the theoretical calculation can effectively shorten the whole investigation period and reduce the cost [16]. In this article, the Na-doped layer-structure Li 1−x Na x Ni 1/3 Co 1/3 Mn 1/3 O 2 is studied theoretically with density functional theory of firstprinciples; the results show that the electrochemical performance of Li 1−x Na x Ni 1/3 Co 1/3 Mn 1/3 O 2 is affected by the proportion of Na-substitution and the best proportion of Nasubstitution in LiNi 1/3 Co 1/3 Mn 1/3 O 2 is in agreement with that of experiments [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the DFT in GGA often underestimate the band gap [21] . Wang and coworkers investigated the conductivity mechanism of nitrogen‐doped LiNbO 3 , [22] they found that the positions of the defect levels related to the valence band maximum(VBM) determined by GGA‐PBE are nearly the same as by HSE06 which was considered a more precise and widely applied method. To investigate the effect of density functional on the results of electronic behavior, Cui et al.…”
Section: Resultsmentioning
confidence: 99%
“…According to our DFT calculations, the energy of N 2 is −22.16 eV, which agrees with the others' calculations. 55,59 We further perform the calculations to determine the formation energies of the N O (the O site is substituted by N atom) and N i (N interstitial) defects in β-Bi 2 O 3 . The results indicate that both N i and N O2 have very high formation energies under the N 2 constraint in Figure 3 (N O1 is not shown as it has a higher formation energy, compared to N O2 ).…”
Section: Intentional Extrinsic P-type N-doping Modification In β-Bi 2 Omentioning
confidence: 99%